2005
DOI: 10.1073/pnas.0507651102
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the KvAP voltage-dependent K + channel and its dependence on the lipid membrane

Abstract: Voltage-dependent ion channels gate open in response to changes in cell membrane voltage. This form of gating permits the propagation of action potentials. We present two structures of the voltage-dependent K ؉ channel KvAP, in complex with monoclonal Fv fragments (3.9 Å) and without antibody fragments (8 Å). We also studied KvAP with disulfide cross-bridges in lipid membranes. Analyzing these data in the context of the crystal structure of Kv1.2 and EPR data on KvAP we reach the following conclusions: (i) KvA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
316
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 293 publications
(329 citation statements)
references
References 22 publications
12
316
1
Order By: Relevance
“…Forcing conditions also result in weak cross-links in two new regions: the S2-S3 turn, which is also known as the membrane interface anchor (positions 164 and 173) (7), and the tip of the voltage sensor paddle (positions 187 and 194) (Fig. 3 c and d) (6).…”
Section: Resultsmentioning
confidence: 99%
“…Forcing conditions also result in weak cross-links in two new regions: the S2-S3 turn, which is also known as the membrane interface anchor (positions 164 and 173) (7), and the tip of the voltage sensor paddle (positions 187 and 194) (Fig. 3 c and d) (6).…”
Section: Resultsmentioning
confidence: 99%
“…HaTx does not interact tightly with either KvAP or Kv1.2, the two Kv channels for which X-ray structures are available, and the sequence similarity between these channels and Kv2.1 is quite low, precluding assignment of crucial residues within the existing structures. The interaction of VSTx1 with chimeras containing the entire paddle of KvAP (Fig 2), however, offers an opportunity to explore the structure of a tarantula toxin receptor because there are three X-ray structures of KvAP 1,8 , and the structure of the paddle motif in these is very similar (whether or not an antibody is bound). To define critical residues within the paddle motif that may interact with VSTx1, we Ala scanned the paddle region of the C*[S3-S4]AP chimera between KvAP and Shaker.…”
Section: Structural Analysis Of the Tarantula Toxin-paddle Interactionmentioning
confidence: 99%
“…It is now recognized that the first KvAP structure was likely distorted by crystallization conditions and its structure has been corrected and shown to be consistent with later structures of other VSDs. 22,23 Following the structure of KvAP, the next VSD to be defined at atomic level and considered a native, non-perturbed structure was part of the now paradigmatic structure of the Kv1.2 mammalian potassium channel. 24 This structure showed that the VSDs interact with the pore domain of an adjacent subunit and stand at the periphery of the whole channel.…”
Section: Introductionmentioning
confidence: 99%